PENGARUH LOAN TO DEPOSIT RATIO DAN KUALITAS AKTIVA PRODUKTIF TERHADAP PENCAPAIAN LABA BANK PERKREDITAN RAKYAT (BPR) DI INDONESIA - Andi Ruslan (Institut Agama Islam Negeri Bone, 2020)
AbstractThis study aims to : ( I ) To analyze the effect Loan to Deposit Ratio ( LDR ) to earnings after tax ( EAT) Rural Bank ( BPR ) in lindonesia ( 2 ) To analyze the effect ofthe quality of earning assets Loans ( KAP - Credit ) to earnings after tar ( EAT) Rural Bank ( BPR ) in lindonesia . ( 3 ) To analyze the effect Loan to Deposit Ratio ( LDR ) and Credit Assets Quality ( KAP - Credit ) simultaneously to earnings gfter tar ( EAT ) Rural Bank ( BPR ) in Indonesia. This study analyzed the effect of the Loan to Deposit Ratio ( LDR ) and the Assets Quality ( KAP ) Credit against net profit qfier tar ( E,4T ) on BPR Indonesia . As for the object of study consists of three variables consist of two (2) independent variables and one (I) dependent variable . independent variable in this study is LDR BPR ( Xl ) Assets Quality ( KAP ) Rural Credit ( ) , while the dependent variable is the net profit after tax of BPR ( EAT ) ( YI ) . The data used beginning in 2000-2012 and analyzed using descriptive statistics , multiple regression analysis using SPSS . The results obtained indicate that ( I ) Variable Loan to Deposit Ratio ( LDR ) no significant effect on profit after tar / Earnings After Tar ( EAT) . but a positive effect . ( 2 ) Variable Credit Assets Quality ( KAP - Credit ) influential significant and positive impact on profit after tar / earnings after Tar ( EAT) . ( 3 ) simultaneously indicates that both variables to Deposit Ratio ( LDR ) and Credit Assets Quality ( KAP - Credit ) significantly influence the profit after tax / Earnings Afier Tax ( EAT ) Kata Kunci: Loan To Deposit Ratio; Aktiva Produktif; Laba Bank.